2021
DOI: 10.1101/2021.02.22.21252219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Associated with Timely Test Seeking, Test Turnaround, and Public Reporting of COVID-19: a retrospective analysis in Ontario, Canada

Abstract: Background Minimizing delays in disease identification and reporting improves the timeliness of surveillance data, and can reduce transmission of COVID-19. Our study investigates factors associated with timely testing and reporting of COVID-19 during the first pandemic wave in one province of Canada. Methods We identified all persons with confirmed SARS-CoV-2 infection residing in private households across the largest province of Canada, Ontario from the date of the first confirmed case in Ontario (January 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…However, the results indicate that compared with females, males have lower likelihood of testing for COVID-19. Our result mirrors that of a related study from Canada 21 that showed that males had significantly lower odds of seeking COVID-19 test compared with females. The observed gender differences in COVID-19 testing could be explained by the risk perception and health seeking behaviour of males.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the results indicate that compared with females, males have lower likelihood of testing for COVID-19. Our result mirrors that of a related study from Canada 21 that showed that males had significantly lower odds of seeking COVID-19 test compared with females. The observed gender differences in COVID-19 testing could be explained by the risk perception and health seeking behaviour of males.…”
Section: Discussionsupporting
confidence: 88%
“…The observed gender differences in COVID-19 testing could be explained by the risk perception and health seeking behaviour of males. 21 22 In a multicountry study, which included the UK, USA, Australia, Germany, Spain, Italy, Sweden, Mexico, Japan and South Korea, it was revealed that males display significantly lower risk perception about COVID-19 compared with females. 23 Such low-risk perception tends to adversely affect males’ health-seeking behaviour including their uptake of COVID-19 testing, thus making males less likely to go for COVID-19 testing.…”
Section: Discussionmentioning
confidence: 99%
“…In general, women carry out hygiene behaviors more frequently [48] and tend to seek medical help more quickly when faced with a health concern [49]. A recent study conducted in Canada analyzing cases of COVID-19 showed that it was women who sought testing promptly to determine whether they were infected by the virus [50].…”
Section: Discussionmentioning
confidence: 99%
“…More positive tests among people marked as “M” with temporary status and permanent residency, combined with lower access to primary care may suggest gendered facets of COVID-19 management, though we cannot measure gender directly due to the way the health system collects this data. Similarly, lower testing rates but higher rates of laboratory confirmed COVID-19 infection, as well as delayed testing were observed among presumed males in Ontario (33,34). In our study, higher testing and visits for COVID-19 related primary care among people with temporary status in rural/remote settings may reflect targeted testing and outreach in agricultural workplaces where people in the Temporary Foreign Worker Program are employed.…”
Section: Discussionmentioning
confidence: 81%